Effect of rosary prayer and yoga mantras on autonomic cardiovascular rhythms: comparative study. Issue 7327 (22nd December 2001) - Bernardi, Luciano; Sleight, Peter; Bandinelli, Gabriele; Cencetti, Simone; Fattorini, Lamberto; Wdowczyc-Szulc, Johanna; Lagi, Alfonso
Abstract: Objective: To test whether rhythmic formulas such as the rosary and yoga mantras can synchronise and reinforce inherent cardiovascular rhythms and modify baroreflex sensitivity. Design: Comparison of effects of recitation of the Ave Maria (in Latin) or of a mantra, during spontaneous and metronome controlled breathing, on breathing rate and on spontaneous oscillations in RR interval, and on blood pressure and cerebral circulation. Setting: Florence and Pavia, Italy. Participants: 23 healthy adults. Main outcome measures: Breathing rate, regularity of breathing, baroreflex sensitivity, frequency of cardiovascular oscillations. Results: Both prayer and mantra caused striking, powerful, and synchronous increases in existing cardiovascular rhythms when recited six times a minute. Baroreflex sensitivity also increased significantly, from 9.5 (SD 4.6) to 11.5 (4.9) ms/mm Hg, P<0.05. Conclusion: Rhythm formulas that involve breathing at six breaths per minute induce favourable psychological and possibly physiological effects.